2000
DOI: 10.1056/nejm200001133420201
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Microsatellite Instability and Clinical Outcome in Young Patients with Colorectal Cancer

Abstract: High-frequency microsatellite instability in colorectal cancer is independently predictive of a relatively favorable outcome and, in addition, reduces the likelihood of metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

52
743
13
28

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,231 publications
(836 citation statements)
references
References 33 publications
52
743
13
28
Order By: Relevance
“…Thus, the proportion of germline MMR mutation carriers in each cohort probably explains differences in tumour distribution and survival reported previously. [1][2][3][4][5][6]33,34 Patients presenting before age 30 years tended to have more advanced malignancy (Dukes' stage C or D, 64% vs. 51%) and a greater proportion of mucinous-type tumours (37% vs. 23%), which is consistent with previous smaller studies. [35][36][37][38][39][40] Although there is evidence that mucinous tumours are more likely to recur locally, there is no convincing evidence for an effect on ultimate survival.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, the proportion of germline MMR mutation carriers in each cohort probably explains differences in tumour distribution and survival reported previously. [1][2][3][4][5][6]33,34 Patients presenting before age 30 years tended to have more advanced malignancy (Dukes' stage C or D, 64% vs. 51%) and a greater proportion of mucinous-type tumours (37% vs. 23%), which is consistent with previous smaller studies. [35][36][37][38][39][40] Although there is evidence that mucinous tumours are more likely to recur locally, there is no convincing evidence for an effect on ultimate survival.…”
Section: Discussionsupporting
confidence: 77%
“…These findings indicate that our understanding of the process of MSI is incomplete and we caution against using MSI alone as a predictor of survival or as a pragmatic tool. 2,34 However, the poor prognosis also underscores the rationale for surveillance of MMR gene carriers in order to detect MSI tumours at an early stage. Thus, these data support surveillance of asymptomatic DNA MMR gene carriers, identified either as part of HNPCC families or by systematic population-based genetic screening approaches.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9] Colon cancer with MSI-H has a better prognosis than other colon cancers; the difference is partly dependent on stage (microsatellite instability-high tumors tend not to produce metastatic disease), but has been found to be independent of stage in some studies. [10][11][12][13][14][15][16] Signet ring cell carcinoma is a rare subtype of colorectal cancer, accounting for 0.1-2.4% of all colorectal malignancy. [17][18][19][20] By definition, more than 50% of tumor cells must have signet ring cell morphology.…”
mentioning
confidence: 99%
“…Numerous studies have shown a survival advantage and a less aggressive clinical course for patients with high frequency MSI. 23,24 Furthermore, MSIhigh tumours have been reported to metastasise less often than microsatellite stable tumours. 24 The MSI phenotype also appears to be associated with excellent survival in patients who receive adjuvant 5FU-based chemotherapy.…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%
“…23,24 Furthermore, MSIhigh tumours have been reported to metastasise less often than microsatellite stable tumours. 24 The MSI phenotype also appears to be associated with excellent survival in patients who receive adjuvant 5FU-based chemotherapy. 25 A recent study found that 61% of stage III CRC patients with MSI-high tumours had a mutation in the gene for the type II receptor for TGF␤-1.…”
Section: Microsatellite Instability (Msi)mentioning
confidence: 99%